Experimental and numerical investigation of the axial performance of GFRP-strengthened concrete columns incorporating red mud and quarry dust as sustainable cement and fine aggregate replacements - Pradeep Thangavel; Jabar Abdul Bari; Divesh Ranjan Kumar; Warit Wipulanusat; Jeung-Hwan Doh (Results in Engineering)
Sustainable materials are becoming increasingly important in the construction sector as a way to solve environmental issues while preserving structural integrity. This study explores the use of red mud (RM) and quarry dust (QD) as sustainable substitutes for cement and fine aggregates in concrete, offering a promising solution for the large-scale utilization of these industrial byproducts. Various replacement levels of RM and QD in cement and fine aggregate were optimized for inclusion in concrete. The axial performance of strengthened glass fiber-reinforced polymer (GFRP) wrapped short columns and unstrengthened short columns was evaluated by replacing RM and QD materials. Compressive strength and stiffness were assessed experimentally for various concrete mixtures, with the best proportions of RM (10 %) and QD (60 %). The results demonstrated that combining RM and QD produced optimal performance for concrete structures. The combination of 10 % RM as cement replacement and 60 % QD as acceptable aggregate replacement resulted in a notable compressive strength of 33.12 MPa, confirming structural viability. The composite mixture enhanced load capacity and ductility of the reinforced columns. GFRP wrapping further increased the load capacity of the short columns. Finite element modelling (FEM) was used to validate the experimental findings, accurately simulating failure modes and stress distributions. Variations in slenderness ratios and GFRP configurations revealed critical insights into buckling behavior and load capacity, emphasizing the influence of column geometry on performance. FEM analysis results closely matched experimental results, validating the numerical model. This study highlights the potential of RM, QD, and GFRP wrapping as sustainable materials.